Preliminary Study of Chitin Extraction from House Crickets (Acheta Domesticus) Through Green Process Using Deep Eutectic Solvent (DES) Chlorine Chloride - Urea - Athirah, Febriana Azhar; Umam, Hilman Imadul; Nur Fadila, Salsabil Intan; Pambudi, Teguh; Perdani, Meka Saima (Universitas Jember, 2024)
Insects serve as a sustainable alternative source of chitin compared to crustaceans, due to their advantages in availability, reproductive rates, and resilience to environmental conditions. Chitin is a natural biopolymer widely utilized in various industries, including food, pharmaceuticals, and biotechnology. This study represents a preliminary investigation aimed at evaluating the effects of varying solution ratios and stirring times on the yield of chitin and the degree of acetylation (DA) obtained from insect chitin extraction using a Green Process with Deep Eutectic Solvent (DES) composed of Choline Chloride (ChCl) and Urea in a molar ratio of 1:2 (w/w). The extraction process involved varying the solution-to-raw material ratios (1:10, 1:15, 1:20) and stirring times (2, 4, 6 hours). Analysis was performed using FTIR to measure DA, and yield calculations were based on the mass comparison before extraction. The results indicated that the DA values and mass yields were lower than those reported in the literature, likely due to residual impurities and the incomplete removal of DES from the samples. The highest DA value of 78.44% was achieved in the sample with a 1:10 ratio and a stirring time of 6 hours, while several other samples exhibited lower DA values due to ineffective deproteinization. This preliminary study provides an important foundation for further research, emphasizing improvements in extraction and purification methods to enhance the quality of the produce.